Essential echocardiography : transesophageal echocardiography for non-cardiac anesthesiologists - Maus, Timothy M.; Nhieu, Sonia; Herway, Seth T. (Springer, 2016)
Covering both transesophageal echocardiography (TEE) and transthoracic echocardiography (TTE), this book fills the need of accessible information for the practitioner seeking a basic level of familiarity with TEE and TTE in the perioperative management of the surgical patient. This book is a practical guide on echocardiography written for non-cardiac anesthesiologists and critical care physicians who wish to become familiar with the use of transesophageal echocardiography (TEE) and transthoracic echocardiography (TTE) as well as a resource for anesthesiologists studying for the Basic PTE examination. Essential Echocardiology also features extensive figures and more than 100 echocardiography videos.